2020
DOI: 10.3390/biom10091268
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoid Nanoparticles: A Promising Approach for Cancer Therapy

Abstract: Flavonoids, a ubiquitous group of naturally occurring polyphenolic compounds, have recently gained importance as anticancer agents. Unfortunately, due to low solubility, absorption, and rapid metabolism of dietary flavonoids, their anticancer potential is not sufficient. Nanocarriers can improve the bioavailability of flavonoids. In this review we aimed to evaluate studies on the anticancer activity of flavonoid nanoparticles. A review of English language articles published until 30 June 2020 was conducted, us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(58 citation statements)
references
References 99 publications
2
56
0
Order By: Relevance
“…Despite this, targeted therapy necessitates the development of methods to precisely deliver anti-cancer compounds. Among numerous attempts to develop such a capacity, nanoencapsulation has been extensively exploited as a novel strategy to deliver anti-cancer drugs particularly for flavonoid phytochemicals due to their poor bioavailability [43,44]. The use of chitosan, rebaudioside A, and directly loading onto gold nanoparticles all have been shown to be feasible approaches and profoundly enhance the anti-cancer activity of chlorogenic or hesperidin [45][46][47][48].…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, targeted therapy necessitates the development of methods to precisely deliver anti-cancer compounds. Among numerous attempts to develop such a capacity, nanoencapsulation has been extensively exploited as a novel strategy to deliver anti-cancer drugs particularly for flavonoid phytochemicals due to their poor bioavailability [43,44]. The use of chitosan, rebaudioside A, and directly loading onto gold nanoparticles all have been shown to be feasible approaches and profoundly enhance the anti-cancer activity of chlorogenic or hesperidin [45][46][47][48].…”
Section: Discussionmentioning
confidence: 99%
“…They showed high potential in the treatment of neoplastic diseases and did not show important side effects. As their bioavailability is low, application avoiding the gastrointestinal tract is recommended [ 146 , 147 ].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, flavonoid and resveratrol, which exist in various dietary sources (vegetables and fruits) have been widely investigated in cancer research. Multiple studies have confirmed that flavonoid possessed vigorous anti-oxidant activity and also had anti-carcinogenic properties (Anwar et al, 2018;Dobrzynska et al, 2020;Moradi et al, 2020). Meanwhile, epidemiological studies have concluded that dietary flavonoid intake was associated with a reduced risk of various cancers, including breast cancer, prostate cancer, and colorectal cancer (Kim et al, 2017;Rodríguez-García et al, 2019;Feng et al, 2020).…”
Section: Keyword Analysismentioning
confidence: 99%